Gene expression in chronic granulomatous disease and interferon‐γ receptor‐deficient cells treated in vitro with interferon‐γ. Issue 3 (27th September 2018) - Frazão, Josias B.; Colombo, Martino; Simillion, Cedric; Bilican, Adem; Keller, Irene; Wüthrich, Daniel; Zhu, Zhiqing; Okoniewski, Michal J.; Bruggmann, Rémy; Condino‐Neto, Antonio; Newburger, Peter E.
Abstract: Interferon‐γ (IFN‐γ) plays an important role in innate and adaptive immunity against intracellular infections and is used clinically for the prevention and control of infections in chronic granulomatous disease (CGD) and inborn defects in the IFN‐γ/interleukin (IL)‐12 axis. Using transcriptome profiling (RNA‐seq), we sought to identify differentially expressed genes, transcripts and exons in Epstein‐Barr virus–transformed B lymphocytes (B‐EBV) cells from CGD patients, IFN‐γ receptor deficiency patients, and normal controls, treated in vitro with IFN‐γ for 48 hours. Our results show that IFN‐γ increased the expression of a diverse array of genes related to different cellular programs. In cells from normal controls and CGD patients, IFN‐γ‐induced expression of genes relevant to oxidative killing, nitric oxide synthase pathway, proteasome‐mediated degradation, antigen presentation, chemoattraction, and cell adhesion. IFN‐γ also upregulated genes involved in diverse stages of messenger RNA (mRNA) processing including pre‐mRNA splicing, as well as others implicated in the folding, transport, and assembly of proteins. In particular, differential exon expression of WARS (encoding tryptophanyl‐transfer RNA synthetase, which has an essential function in protein synthesis) induced by IFN‐γ in normal and CGD cells suggests that this gene may have an important contribution to the benefits of IFN‐γ treatment for CGD. Upregulation of mRNA and protein processing related genes in CGD and IFNRD cells could mediate some of the effects of IFN‐γ treatment. These data support the concept that IFN‐γ treatment may contribute to increased immune responses against pathogens through regulation of genes important for mRNA and protein processing. Abstract : Interferon‐γ (IFN‐γ) plays an important role in innate and adaptive immunity against intracellular infections and is used clinically for the prevention and control of infections in chronic granulomatous disease (CGD) and inborn defects in the IFN‐γ/interleukin (IL)‐12 axis. Our gene expression profiling studies show that IFN‐γ increased the expression of a diverse array of genes related to different cellular programs. These data provide a biochemical basis for the cytokine's contributed to increased immune responses against pathogens through regulation of genes important for messenger RNA and protein processing